1994
DOI: 10.1093/oxfordjournals.humrep.a138492
|View full text |Cite
|
Sign up to set email alerts
|

Decidualization of human endometrial stromal cells in vitro: effects of progestin and relaxin on the ultrastructure and production of decidual secretory proteins*

Abstract: Decidual cells arise by proliferation and differentiation of endometrial stromal cells of the uterus after appropriate stimulation by ovarian hormones. Previously we have shown that progestin and relaxin stimulate the secretion of several decidual-cell-specific secretory proteins in a long-term primary cell culture system. We now report the effects of progestin and relaxin on the morphology of stromal cells in association with the production rate of two major decidual secretory proteins, prolactin and insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…Thus, relaxin seems to be a powerful regulator of human endometrial decidualization, at least as influential as progesterone, if not more so. No evidence of secretory activity was shown by cells treated with only progesterone and estradiol, although secretory activity appears to be a prominent feature of decidualized endometrial stromal cells in vivo (21). Cells in the stromal cultures that were treated with relaxin in addition to progestin exhibited ultrastructural features characteristic of secretory cells.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Thus, relaxin seems to be a powerful regulator of human endometrial decidualization, at least as influential as progesterone, if not more so. No evidence of secretory activity was shown by cells treated with only progesterone and estradiol, although secretory activity appears to be a prominent feature of decidualized endometrial stromal cells in vivo (21). Cells in the stromal cultures that were treated with relaxin in addition to progestin exhibited ultrastructural features characteristic of secretory cells.…”
Section: Discussionmentioning
confidence: 86%
“…Results from various studies provide abundant evidence that relaxin is a potent regulator of the differentiated function of human endometrial cells in vitro (14,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Relaxin stimulates the production of prolactin (16,17,19), insulin-like growth factor (18), and insulin-like growth factor binding protein 1 (IGFBP-1) (19), in progestin-primed endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA microarray studies have shown that FOXO1A is targeted to the nucleus of human decidual cells (Christian et al 2002) and is one of the earliest and most induced genes during human decidualization (Brar et al 2001). In addition, transfection studies in human decidual cells have shown that overexpression of FOXO1A induces expression of the prolactin (Christian et al 2002) and insulin-like growth factor-binding protein 1 (IGFBP-1; Lane et al 1994, Tseng et al 1997, Kim et al 2005 genes, both of which are markedly induced during human decidualization. In a recent study, Kim and co-workers (2005) also reported that a FOXO1A small interfering RNA (siRNA) blocked IGFBP-1 expression in human uterine fibroblasts and HEC-1B cells, but they did not examine whether silencing of FOXO1A expression affects other markers of decidualization and is important in the induction of the decidualization process.…”
Section: Introductionmentioning
confidence: 99%